Assessing the Coverage of Health Care Facilities in Surakarta using the Hierarchical Maximal Covering Model: Case Study. (April 2019) - Yuniaristanto,; Fauzan, M I R; Hisjam, M
Abstract: The assessment of optimal health location becomes one of the main concerns of developing countries to avoid the occurrence of epidemic diseases that can reduce the quality of life of the community. The purpose of this study is to assess the ability of the existing health facility in Surakarta City, Indonesia to serve the available demand based on the hierarchy of National Health Insurance Program (NHIP). The assessment is modelled by using integer linear programming called model of capacitated hierarchical maximal covering. The results of this study found that not all of the existing demand has been able to be served by the existing health facilities. At the first level, it is found that not all communities in Banjarsari district could be served by Basic Healthcare Unit or Family Doctors because of their capacity are not sufficient to serve all demand. While at the fourth level, demand from Kasih Ibu Hospital could not served by dr. Moewardi Hospital because the distance between the two hospitals exceeds the allowed critical distances.